Accuracy of Periapical Radiography for Detection of Alveolar Osseous Defect in Relation to their Anatomic Location - A - Zamaninaser; I Zyhajehzadeh; E Khayam (Isfahan University of Medical Sciences, 2006)
Introduction: Radiographs are of limited value in diagnosis of osseous defects. Anatomic and technical factors affect the radiographic appearance of bone lesions. In this research radiographic appearance of alveolar osseous defects in relation to their anatomic location is evaluated by periapical radiography.Methods and materials: Experimental bone lesions were created in the eight location of alveolar process of a skull. Standardized periapical radiographs were obtained before and after the defects were made. After processing, pairs of radiographs were randomly mounted. Four dentists acted as observers in order to determine whether or not a change in alveolar bone was detectable at each of the eight possible locations. Finally, the twenty Radiographic images taken from each location were randomly arranged and mounted in ten pairs and four dentists were asked to determine whether or not a change in alveolar bone was detectable at each of eight possible locations.Results: After evaluation of the data and statistical analysis, it was concluded that the prevalence of the correct diagnosis in mandibular lesions in contrast with maxilla, and in lingual aspect in contrast with the buccal aspect of the alveolar bone, and in marginal bone in contrast with interproximal region is definitely more.Conclusion: The results showed that the anatomic location of a lesion in the alveolar bone did affect its radiographic appearance. Furthurmore, experimental defects were detected more often in the mandible and on the lingual surface of the alveolar crest and on the marginal bone.Key words: Periapical radiography, Anatomic location, Osseous defects.